Evolution of Floral Fragrance Is Compromised by Herbivory - Ramos, Sergio E.; Schiestl, Florian P. (Frontiers in Ecology and Evolution, 2020)
Despite the paramount role of floral fragrance in pollinator attraction and reproduction in flowering plants, we know little about its evolution under natural conditions. Here we show that by reducing herbivore load with pesticide application, plants evolved more fragrant flowers within 4 generations compared to plants with normal figures of herbivory. We interpret this finding in the context of relieved physiological and ecological trade-offs with fewer herbivores, selecting for increased floral signaling in plants. Our study confirms earlier findings of experimental evolution under highly controlled and simplified conditions in the greenhouse.